Gastrodia elata Blume extract improves high-fat diet-induced type 2 diabetes by regulating gut microbiota and bile acid profile - Wang, Danqi; Wang, Jun-Xia; Yan, Chunri; Liu, Yize; Liu, Hongye; Li, Dongxu; Zhu, Jun; Luo, Zhao-Bo; Han, Sheng-Zhong; Jin, Zheng-Yun; Chang, Shuang-Yan; Yang, Liu-Hui; et al. (Frontiers in Microbiology, 2022)
In this study, we aimed to characterize the anti-type 2 diabetes (T2D) effects of Gastrodia elata Blume extract (GEBE) and determine whether these are mediated through modification of the gut microbiota and bile acids. Mice were fed a high-fat diet (HFD), with or without GEBE, and we found that GEBE significantly ameliorated the HFD-induced hyperglycemia, insulin resistance, and inflammation by upregulating glucose transporter 4 (GLUT4) and inhibiting the toll-like receptor 4-nuclear factor kappa-B signaling pathway in white adipose tissue (WAT). In addition, we found that GEBE increased the abundance of Faecalibaculum and Lactobacillus, and altered the serum bile acid concentrations, with a significant increase in deoxycholic acid. The administration of combined antibiotics to mice to eliminate their intestinal microbiota caused a loss of the protective effects of GEBE. Taken together, these findings suggest that GEBE ameliorates T2D by increasing GLUT4 expression in WAT, remodeling the gut microbiota, and modifying serum bile acid concentrations.